Strategi Perencanaan Sumber Daya Manusia Dengan Metode Analisis SWOT Di PT X (Distributor Rokok Terbesar Di Indonesia) - Sapitri, Dian; Oktovian, Evan Nur; Mulyadi, Adi; Saputra, Agung Aditya (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2022)
This research aims to find out how the human resource planning strategy conducted by PT X Cigarette Distributor. This company is a cigarette distributor company and is the largest cigarette "brand" in Indonesia, because it is a large company so there is also a lot of labor in it. So in this study analyzed whether existing human resources are effective or not. The type of research conducted is Field Research which is descriptive analysis that is research that describes the strategy of human resource planning in an effort to improve employee performance. Data collected by interview, observation, and documentation. Data analysis techniques used qualitative descriptive analysis combined with SWOT analysis approach. The results of the study explain that in human resource planning there are several stages in the process of procuring new employees. And in carrying out its operational activities, the company considers the strengths, weaknesses, opportunities and threats that one day can benefit or harm the company.